ANALISIS KESALAHAN SISWA DALAM MENGERJAKAN SOAL PENJUMLAHAN DAN PENGURANGAN PECAHAN BERDASARKAN KRITERIA WATSON - Dedi Pramada; Hajerina Hajerina (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2020)
This study aims to determine the criteria for errors made by students at SDN 7 Sindue in solving story problems on fraction operations based on Watson's theory. The research subjects consisted of 3 students, each of whom had high, medium, and low abilities according to the ranking obtained. Based on the results of research conducted, the criteria for errors that are mostly carried out by students based on Watson's theory are error type Id (incorrect data), Ip (incorrect procedure), Od (missing data), Oc (missing conclusion), Rlc (level conflict response), Um (Indirect manipulation), Shp (Skills hierarchy). And the most common mistakes made by subjects 1, 2, and 3 are IP (Inappropriate Procedure), and RLC (Response Level Conflict) errors.